Dynamics of monsoon trough over northwest and adjoining westcentral Bay of Bengal (MAUSAM, 2004)
Daily variations of surface and thermodynamical parameters in the vicinity of eastern end of the monsoon trough located over northwest and adjoining westcentral Bay of Bengal have been studied.  A model sequence for the strengthening/weakening of the monsoon trough over head Bay of Bengal, which is the seat of cyclogenesis during southwest monsoon, has been proposed.  Monsoon trough activity over the sea seems to possess a 4 day cycle.  The primary forcing for the activation of monsoon trough appears to be the sea surface temperature (SST).  The lag between peak SST and minimum surface pressure appears to be 2 days.  The lag between peak SST and enhanced rainfall over Orissa seems to be 4 days.